Storage of cowpea under farmer level - Aguiar, Paulo Anselmo A.; Moraes, Gilberto J. de (Pesquisa Agropecuaria Brasileira, 2014)
Cowpea (Vigna unguiculata (L) Walp) seeds were stored with a slight weevil (Callosobruchus maculatus) infestation (1.5 - 3%) for a twelve-month period, under low humidity and high temperature in the northeast Brazil. Five containers were used: 1. amianthus box with sand cover; 2. metallic bin sealed with bee wax; 3. subterraneous bin with plastic covering; 4. jute sack with seeds sprayed with corn oil; 5. jute sack. A great attack of the weevil in jute sacks during the storage period was detected while the other containers offered a good protection against the pest attack, mainly in the amianthus box with sand cover.
Keywords: losses in storage; weevil; Callosobruchus maculatus; germination; vigor; Vigna unguiculata